Evaluating the Solar Radiation System under the Climatic Condition of Dhaka, Bangladesh and Computing the Angstrom Coefficients - Rashid, MA; Mamun, RA; Sultana, J; Hasnat, A; Khan, KA; Rahman, M (International Journal of Natural Sciences, 2012)
In this research work some mathematical models have been simulated to estimate the regression coefficients, which are also known as Angstrom coefficients, with monthly and daily average solar radiation on horizontal surface using bright sunshine hours. This study of solar energy, information on solar radiation and its components at a given location is very essential for scientists, engineers, architects, agriculturists and hydrologists for various applications such as measuring aerosol optical thickness, solar heating, cooking, drying and interior illumination of buildings. But, for developing countries like Bangladesh, we have limitation of sophisticated measuring instruments. So, we have used some latitude based empirical models to calculate an important solar radiation geometry parameter- Angstrom Coefficients for Bangladesh without any help of costly instruments. DOI: http://dx.doi.org/10.3329/ijns.v2i1.10882 International Journal of Natural Sciences (2012), 2(1): 38-42